Connectionless protocol: a localised approach to wireless ad hoc networks. (7th December 2006) - Ho, Yao H.; Ho, Ai Hua; Hua, Kien A.
Most mobile ad hoc network's communication techniques need to discover routes and establish a connection before they can communicate. This strategy cannot robustly adapt to frequent unpredictable topology changes due to high mobility. Constant reconnections incur significant overhead making these schemes unsuitable for applications such as voice and video. To address these issues, we explore a connectionless paradigm in this paper. By leverage GPS technology, data packets are relayed along the general direction to packets' destination using different intermediate nodes at different times without having to first establish a connection. The performance of this solution is essentially unaffected by node mobility.